The Effectiveness of Low-Level Laser Therapy in Treating Tinnitus: A Randomized Controlled Trial - Bashir, Amna; Khan, Nusara; Adeel-Ur-Rehman; Lohana, Priya; Shiblee, Syeda Areeba; Asif, Neha (Indus Journal of Bioscience Research, 2025)
This study aimed to evaluate the effectiveness, safety, and patient satisfaction associated with Low-Level Laser Therapy (LLLT) in the management of chronic tinnitus. A total of 78 adults (39 in the LLLT group and 39 in the Placebo group) suffering from chronic tinnitus (lasting at least 6 months) were randomly assigned to either the treatment or placebo group. A randomized controlled trial design was employed, with pre- and post-treatment tinnitus severity measured using the Tinnitus Handicap Inventory (THI) and Visual Analog Scales (VAS). Data were analyzed using Paired t-tests to compare within-group changes, ANCOVA to control for baseline severity, and Chi-square tests to assess safety, tolerability, and patient satisfaction. The results showed that the LLLT group experienced significant improvements in tinnitus severity, with post-treatment THI scores significantly lower than pre-treatment scores (p = 0.001). Additionally, LLLT was associated with higher patient satisfaction (76.9% vs. 64.1%) and fewer adverse effects (7.7% vs. 20.5%) compared to the placebo group. The study concluded that LLLT is an effective, safe, and well-tolerated treatment for chronic tinnitus, offering significant relief and high patient satisfaction. Further research is recommended to explore the long-term effects and optimize treatment protocols for broader clinical application. In conclusion, this study confirms the effectiveness and safety of Low-Level Laser Therapy (LLLT) in reducing tinnitus severity. Significant improvements were observed using THI and VAS scores. LLLT was well-tolerated with minimal side effects. These findings support LLLT as a promising therapeutic option for chronic tinnitus, though further research is needed to optimize treatment parameters and assess long-term outcomes.